Multifaceted Instructional Leadership of School Principals to Improve Student Character in The Digital Era - Mustari, Mohamad; Nurhayati, Sri (Letiges, 2024)
This research explores the multifaceted role of principals' instructional leadership in fostering student character development. This research was conducted at the Junior High School (SMP) Muhammadiyah Boarding School in Masbagik, East Lombok, using a qualitative and case study approach. The researcher collects data through interviews, observation, and document analysis. Data analysis using the Miles and Huberman data reduction model, data presentation, and drawing conclusions or verification distils the main dimensions of leadership and their influence on character education. The informants for this research were the school principal, teachers and school committee. These findings reveal eight distinct leadership roles: strategic visionary, educational innovator, adaptive problem solver, evaluator, community builder, cultural architect, responsive adapter, and long-term strategist. Each role makes a unique contribution to student character development. These roles collectively contribute to the character-centred ethos of education and are corroborated by current instructional leadership research. This study offers valuable insights and implications for improving character education through adaptive and nuanced leadership practices, making significant contributions to the broader discourse on instructional leadership and character development in education.